THE INCLUSION OF STUDENTS WHO ARE THE TARGET-AUDIENCE OF SPECIAL EDUCATION IN PRIMARY SCHOOL I THROUGH THE EYES OF THE TEACHERS - Carbone Carneiro, Relma Urel [UNESP]; Uehara, Flavia [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
This study had the aim to analyze how school inclusion of students who are the target-audience of Special Education has been taking place in the initial grades of Primary School. For this purpose, we developed a qualitative research that used Case Study as the methodological procedure. We applied a questionnaire to 13 teachers of regular classes working at a municipal school from an inland town in Sao Paulo state who had in their classes some students with disabilities. Results demonstrated that the mere enrollment of a student with disability in the regular classroom does not mean they are included in the class and that the teachers' concept of such inclusion is, most of the times, negative; teachers do not experience themselves as the agents of the necessary changes, they demand training, besides structural, pedagogical and human support. Our conclusion is that school inclusion is part of a movement that assumes change of model, structure and politics and builds itself from inside out, with critical analysis of what is proposed and propositional reflexion on where we are going.
Keywords: School inclusion; Teaching work; Primary school I